A Bibliometric Analysis on Supply Chain Collaboration - Tripathi V.; Singh K.; Parihar S.; Srivastava S.K. (My University, 2025)
Supply Chain Collaboration (SCC) has been a topic of great interest among the supply chain researchers for decades now. Collaboration among channel-partners is imperative for successful supply chain management and may be the most critical core competency for enhancing the supply chain performance. This paper examines the various SCC frameworks and their development through a bibliometric analysis of the SCC literature published under the Web of Science (WoS) database in the last twenty years from 2003 to 2022 (including early access for January, 2023) comprising of 4249 research articles. The analysis and graphical visualization of the bibliometric data is presented using measures of descriptive statistics and visualization tools identifying the linkages between the published literature. This study analyses the distribution of the publications based on the research author analysis, most cited publications analysis, publication source analysis, country-wise literature analysis and the keywords co-occurrence analysis. The study also examines the most cited researches on SCC in last two decades and attempts to collate the major developments in the SCC knowledgebase. This research corroborates the enormity of the research conducted in the past and accentuates the ever-growing significance of collaboration in the supply chains for future researchers and businesses worldwide. On an average more than two hundred articles are published every year on SCC and the time-series forecasts reaffirm its progressiveness and relevance as a research domain more than ever engaging researchers and business organisation across the globe. The systematically collated data of top twenty most cited articles, authors, journals, keyword and countries involved in SCC research has been prepared which will provide a source of practical reference for the early supply chain researchers and professionals globally. © 2022, School of Management Sciences. All rights reserved.